Halloysite in Argentinian deposits: origin and textural constraints - Cravero, Fiorella (2012)
In Argentina, the only halloysite deposits found so far are located in the southwest of the province of Rio Negro. The areas are named Mamil Choique and Buitrera, separated 50 km in W-E direction. The deposits are located in pyroclastic rocks, rhyolitic tuffs and ignimbrites. The aim of this paper is to determine the origin of the alteration, if there is a relationship between the process in Mamil Choique and Buitrera and which are the factors that controlled the halloysite formation. The work was based on field work, mineralogical and geochemical studies, form and distribution of the alteration. Fresh as well as altered rocks were collected. The first was studied by petrographic and chemical methods. In altered samples, clay mineralogy was determined by XRD and textures by SEM and TEM. Chemical analyses on fresh and altered samples were used to characterize the alteration process and the rock composition. It was concluded that halloysite has been formed by weathering in a time range from Middle Eocene to Middle Oligocene and extended along 50 km in W-E direction, independently of the source rock. Particle morphology depends on the original texture of the rock, spheroidal halloysite is related to rocks with low porosity and tubular particles are related to rocks with open spaces.